MacIntyre and the Challenges of Higher Education in the 21st Century - Miguel Angel Belmonte (Ignatianum University Press, 2020)
Reflection on the nature of the university and its role in contemporary society occupies an important place in the work of the philosopher Alasdair MacIntyre. His academic career and his view of the incommensurable nature of moral discourses combine to suggest an original and provocative proposal for a new model of higher education. This model is characterized by a unity based on a philosophical and theological formality capable of dispelling the dangers of fragmentation and utilitarian specialization. In MacIntyre's proposal, the university becomes the most important vehicle for organizing knowledge and, consequently, for ordering social life.